Aplikasi Simulasi Tambak Ikan Berbasiskan Mobile untuk Meningkatkan Minat Kewirausahaan - Budi Yulianto; Lusiana Citra Dewi; Erlangga Damar Prayoga; Rizky Arif Budiman (Bina Nusantara University, 2013)
The background of the research is that mobile phone based application growth is not as increasing as its education category for improving users’ entrepreneurial-interest, especially in fishpond. The goal of the research is designing an application as a digital game based education tool that can simulate fishpond to users. Output of the research is a mobile application that can deliver information of fishpond system as basic entrepreneurship knowledge to users. On the development phase, the research uses literature study and user requirement analysis. Conclusion of the research has shown that the developed application is based on multimedia and game and also can deliver basic information of fishpond to users such as preservation, purchasing, and selling. The application is developed with good-looking interface and easily-covered level of difficulty.